Blueprint for A New Democracy: Dambisa Moyo. (2018). Edge of Chaos: Why Democracy is Failing to Deliver Economic Growth – and How to Fix It (New York: Basic Books) - Irwanto, Eristya Puspitadewi (Journal of Indonesian Social Sciences and Humanities, 2018)
-